The Relationship Impacting Coping Strategies, Anxiety, and Learning Stress in Eleventh-Grade English Students - Herman, Marliah Ananda; Budiyanto, Darmawan; Setiawan, Heru; Ridho, M.Rasyid (CV. Doki Course and Training, 2023)
The purpose of this research to coping method and anxiety has any kind of meaningful relationship, there was a connection between them that was meaningful coping strategy and anxiety of English is being taught to students in the eleventh grade at SMA Negeri 2 Palembang., there was any significant correlation between coping strategy and learning stress of the eleventh graders is in learning English at SMA Negeri 2 Palembang, how much did coping strategy contribute toward anxiety of the eleventh graders is in learning English, how much did coping strategy contribute towards anxiety and learning stress in students eleventh graders of learning English. This researched used experimental study with correlational approach, In order to collect data for this research, the writer used cluster sampling to select 420 students from the population of the study in the eleventh grade at SMA Negeri 2 Palembang. Questionnaire and analyzing the data used correlation study and spearman correlation. The result of this study was to found out the regression analysis and got score of 0,562. It can be concluded that there was correlation between students' coping strategy and anxiety. The result that the correlation using Shapiro-Wilk test for Anxiety 0,000, and the significance coefficient (Sig -2tailed) of Shapiro-Wilk for learning stress 0,000 and it’s lower than 0,05.It means that the normality of data was rejected because the data used Spearman correlation.